Contribution to an anaerobic digester heating using solar energy, under cotonou temperature conditions - HOUNGUE, Cessac Franck Clair; HOUNGAN, KOKOU THÉOPHILE; ADJOVI, EDMOND CODJO (My University, 2017)
One of the challenges that the scientists are facing, is the energy issue. In such a context, news technologies of energy are motor of innovation [1]. Renewable energies are placed in pole position of these new energy technologies and are increasingly stretched. Among these renewable energies, anaerobic digestion remains a renewable source of energy that is more accessible to people, especially rural communities. Anaerobic produces biogas (mainly formed of: 50% to 70% methane for 30% to 50% CO2) by the degradation of organic matter in the absence of oxygen and under the effect of microorganisms. This transformation of organic matter into methane is done in several steps (hydrolysis, acid formation, acetone formation and methane formation). The methane formation process is done over several days. Its duration, in the case the process evolves in natural conditions, is dependent on the mass, the type and the dry matter content of the material to digest. For instance, 130L of organic matter may last one month[2].The methane formation duration is linked to many factors including pH, alkalinity, and temperature[3]. Furthermore, it is known that raising the temperature in the digester, could increase the growth rate of methanogenic bacteria, and therefore increase the kinetics of methane production [4]. In Benin country, anaerobic digestion starts to develop. But the monthly average level of daily irradiations are 3.9kWh/m2 to 6.2kWh/m2 and the sunshine duration is 4.5 to 6 hours by day[5].
Keywords: Anaerobic digestion; Solar heating; Cotonou city temperature conditions; Hardware in the Loop